(untitled) (Journal of Governance and Development (JGD), 2022)
This study examines the effect of institutional governance on the financial performance of National Microfinance Banks (NMFBs) in Nigeria for the period 2016 to 2021. Institutional governance was proxy by Board characteristics such as board size, board independence, board gender diversity, and audit committee size while financial performance was measured by the returns on assets (ROA). The study adopts a descriptive research design while panel multiple regression was used to test the hypotheses of the study. The study found that board size and board gender diversity have significant negative effects on financial performance while board independence and audit committee size have significant positive effects on the financial performance of the sampled banks. From the findings, the study concludes that institutional governance variables have a significant effect on the financial performance of the NMFBs in Nigeria. It is recommended that NMFBs should have a board with at least six non-executive directors to guarantee board independence. The study also recommends that an audit committee size of at least four will help to enhance the financial performance of the NMFBs.